Predisposing factors analysis of mandibular anterior tooth crowding in the mixed dentition period by the tooth size and dental arch width - Indriyanti, Ratna; Efendi, Sjarief Hidajat; Maskoen, Ani Melani; Riyanti, Eriska (Universitas Padjadjaran, 2018)
Introduction: Tooth crowding can cause complaints if not treated early — this condition resulting in aesthetic disorders, and also masticatory and speech function disruption. The study was aimed to determine the predisposing factors of tooth crowding in the mixed dentition period by the tooth size and dental arch width. Methods: Research type was random cross-sectional. The sample was as much as 29 children with mandibular casting; then the mandibular model cast of these 6 – 9-years old children were divided into two groups according to the crowding condition in the mandibular anterior region, and the measurement was performed afterwards. Space available category was (A/A1), mesiodistal width of mandibular incisor (B/B1), total arch length (C/C1), intercanine width (D/D1), first primary intermolar width (E/E1), second primary intermolar width (F/F1), first permanent intermolar width (G/G1), interalveolar width (H/H1). Result: The results of the t-test showed significant differences (p < 0.05) in the available space for 4 incisors, where the space was larger in the non-crowded group with a difference of 2.22 mm and the mesiodistal sizes of these 4 incisors was larger in the crowded teeth group, with the difference of 1.8 mm. The results of the Pearson correlation coefficient showed a positive relationship to several measurements, namely D to C1, E to D1 and H to B1, C1, D1, F1 and G1, with the t-value > 3 and the r-value was closer to 1, which showed a correlation with strong closeness degree (r > 0.61). Conclusion: Predisposing factors of tooth crowding in the mixed dentition period were the first intercanine width (D), first primary intermolar width (E), and alveolar arch width (H).Keywords: Tooth crowding, arch dimension, mixed dentition period.